EKSPLORASI ETNOMATEMATIKA PADA UDENG KHAS BANYUWANGI - Elok Faiqotul Himmah; Sumartono Sumartono; Windi Setiawan (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
Indonesia is a country that has a variety of cultures. One form of cultural diversity that must be maintained in order to remain sustainable is udeng. There are many ways that can be done to keep udeng from becoming extinct. One way that can be done is to use udeng on certain events or in everyday life. But something more specific to preserve udeng can be done by involving it in learning mathematics. One of the udeng that can be used is the typical Banyuwangi udeng. This article was written using a literature study, discussing ethnomathematics that can be used as a reference in learning. Several examples, one of which is Udeng Banyuwangi, will be described in detail as a reference for completing future research.